The Concept of Gender Justice from the Perspective of Indonesian Women Ulama - Siti Nikhayatul Ma'unah (The Institute of Research and Service Community IPMAFA Pati, 2021)
Gender differences are unimportant as long as they do not result in gender inequality. However, it turns out that gender disparities have resulted in a variety of injustices, which affect both men and women. Gender inequality is a system and structure that affects both men and women equally. Because Islam is based on a relationship between Allah and individual women and men, the Qur'an's concept of Islam treats both women and men equally. According to Islamic normativity, a person's high and low quality is determined solely by his or her level of devotion to Allah. Humans are treated equally by God, who does not distinguish between them. God does not differentiate between men and women when it comes to the works he performs. Gender equity is a necessity for both men and women, according to Indonesian women researchers.